Senam Asma Indonesia dalam Perspektif Rehabilitasi Medis - Widjanantie, Siti Chandra; Laras, Sekar; Damayanti, Triya; Nusdwinuringtyas, Nury; Yunus, Faisal (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
“Senam Asma Indonesia” (SAI) is a series of medical knowledge-based structured physical exercises invented by a multidisciplinary team incorporated in the Indonesian Asthma Foundation (YAI) in 1994, taking into account the characteristics of asthma patients adjusted to the severity of the asthma diagnosis with different loads at each stage. The principles for treating asthma are avoidance of triggers, using medication, and maintaining physical fitness. The quality of life (QoL) of asthma patients decreases due to limited daily life activities caused by the respiratory symptoms they suffer. Multifactorial symptoms of asthma such as limited ventilation, gas transfer abnormalities, pulmonary and cardiac blood vessel dysfunction, and dysfunction of extremity muscles, will cause shortness of breath during physical activity or exercise, which is known as Exercise-induced Bronchoconstriction (EIB). Oral steroid therapy given to treat acute exacerbations can cause steroid-induced myopathy and skeletal muscle remodeling, resulting in decreased muscle endurance. SAI consists of a series of movements designed to improve lung function, strengthen respiratory muscles, and improve the quality of life of asthma patients. From a medical rehabilitation perspective, SAI can contribute to optimizing thoracic wall mobility, respiratory control with pursed-lip breathing, relaxation, and improving cardiorespiratory fitness.